Analisis Strategi Pengembangan Produksi Komoditas Tomat Ceri Organik di PT Cetro Tama Indonesia Kabupaten Semarang - Fitriani, Amelia Rizky; Setiyawan, Hery; Budiraharjo, Kustopo (Universitas Galuh, 2025)
PT Cetro Tama Indonesia is a company that offers various organic and non-organic vegetable commodities, one of which is cherry tomatoes. The problem faced is that demand from consumers of cherry tomatoes continues to increase but production is still low so that it cannot meet consumer demand. This study aims to analyze internal and external factors and formulate alternative strategies and priorities in developing an organic cherry tomato business for the company. The research method used is the case study method because this research only focuses in depth on one research object. The respondent sampling method used purposive sampling method with a total of 7 respondents, namely 4 from the company and 3 from farmer partners. The data used are primary data and secondary data with data collection using interviews, observation, and documentation methods. The data analysis methods used are SWOT analysis, IFAS, EFAS, and QSPM. The results of this study show that the results of the analysis of internal factors owned by the company obtained that the main strengths are having business licenses and organic certificates, organic cherry tomato products do not use chemicals, farmer partners are experienced in organic vegetable cultivation and have the Cetrofarm logo and brand as a product identity while the main weaknesses of the company are the company does not have its own garden and dependence on cherry tomato suppliers that are at risk of production fulfillment. The results of the analysis of external factors obtained that the main opportunity is partnering with supermarkets, restaurants, and other food companies while the company's main threat is weather and climate changes that affect cherry tomato production. The highest priority alternative strategy is to cooperate with other farmer partners with the aim of increasing the volume of cherry tomato production in order to meet consumer demand.